Reading Beyond the Textbook through Epic! : A Digital Platform to Engage EFL Learners - Devi Amaresta; Rojab Siti Qodliyah; Finita Dewi (Badan Penerbit STIEPARI Press, 2026)
This study explores the use of Epic!, a digital reading platform, as a medium to promote student engagement in English as a Foreign Language (EFL) classrooms. Implemented through two cycles of Classroom Action Research (CAR), the study examined how digital reading activities could improve students’ behavioral, emotional, and cognitive engagement. Data were collected through classroom observations, interviews, and document analysis, then analyzed thematically to trace changes across the learning cycles. The findings indicate that Epic! created a more dynamic and participatory learning atmosphere, encouraging students to take a more active role in reading. In the first cycle, learners displayed enthusiasm but depended largely on teacher direction. By the second cycle, they demonstrated stronger autonomy, confidence, and reflection in their reading practices. Although technical challenges such as internet instability and limited device access were encountered, the platform effectively fostered motivation and sustained participation. The study concludes that Epic!serves as an engaging and practical digital resource that promotes meaningful, independent, and enjoyable reading experiences for EFL learners.